Trichome morphology of Ajuga orientalis L. (Lamiaceae) from Turkey (Bangladesh Journal of Botany, 2014)
Morphology and localization of the trichomes on vegetative and reproductive organs of Ajuga orientalis L. from Turkey were investigated. Peltate, capitate glandular and non-glandular trichomes were found on the stem, leaf, petiole, calyx and corolla surfaces of A. orientalis. Three sub-types of capitate glandular trichomes were found whereas two sub-types of non-glandular ones were stated on the several organs of A. orientalis. Glandular trichomes were mainly observed on calyx and corolla, but non-glandular ones were found on the stem, leaf surface and petiole. DOI: http://dx.doi.org/10.3329/bjb.v43i1.19754 Bangladesh J. Bot. 43(1): 91-95, 2014 (June)